2007
DOI: 10.1051/vetres:2006040
|View full text |Cite
|
Sign up to set email alerts
|

Immunostimulatory properties of a novel adjuvant administered with inactivated influenza virus vaccine

Abstract: -The immunopotentiating activity of a new delivery system was investigated comparatively to Alhydrogel adjuvant, as an antiviral inactivated vaccine after one injection. The efficiency of the new formulation (BioMed) was evaluated with an inactivated porcine strain of influenza (A/Sw/IN/1726/88 H1N1) in the pig model. The first assessment criteria was the follow-up of selected immunological parameters such as, antibody levels, lymphoproliferation, double positive CD4 + CD8 + T lymphocytes and cytokine producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
2
0
1
Order By: Relevance
“…The overuse and oftentimes the misuse of β-lactams antibiotics are the most important factors promoting the selection and emergence of β-lactam-resistant bacteria in both human and veterinary medicine [ 1 ]. The first β-lactamases, TEM-1, TEM-2 and SHV-1 were found in Escherichia coli and Klebsiella pneumoniae strains and described in the early 1960s, about 15 years after the wide use of penicillin.…”
Section: Introductionmentioning
confidence: 99%
“…The overuse and oftentimes the misuse of β-lactams antibiotics are the most important factors promoting the selection and emergence of β-lactam-resistant bacteria in both human and veterinary medicine [ 1 ]. The first β-lactamases, TEM-1, TEM-2 and SHV-1 were found in Escherichia coli and Klebsiella pneumoniae strains and described in the early 1960s, about 15 years after the wide use of penicillin.…”
Section: Introductionmentioning
confidence: 99%
“…Failure to anticipate the emergence of an epidemic strain with significant antigenic changes compared to the vaccine strain will greatly reduce vaccine-induced protection. Several studies have suggested that proper adjuvant might improve the immunity of influenza vaccine and reduce the dose of vaccine [5-10]. Aluminum hydroxide (alum) is currently the only human vaccine adjuvant approved for use in the United States, and although it is effective at boosting antibody responses, these responses require repeated administration and tend to generate antiparasitic T helper 2 (T H 2), rather than antiviral and antibacterial T H 1, T cell immunity [11].…”
Section: Introductionmentioning
confidence: 99%
“…Por exemplo, as vitaminas A, D e E, possuem propriedades imunomoduladoras, atuando em vários mecanismos de ativação da resposta imune (CHUA e HANSEN, 2012;LIU at al., 2006;MORA et al, 2008;VERMA et al, 2014;WELLEMANS et al, 2007  Avaliar a existência, ou não, de toxicidade induzida pelas formulações vacinais estudadas;…”
Section: Introductionunclassified